PEMBENTUKAN PERSONAL BRANDING DI MEDIA SOSIAL TIKTOK (Studi pada @dilanjaniyar_2) - Putri Maharani, Rr Imelda; Mardiana, Lisa (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2024)
Personal branding is where someone promotes themselves as a unique brand and has added value in a certain field. Personal branding involves choosing the right platform to promote yourself such as social media. TikTok social media has now become a very popular platform for building personal branding. Dilan Janiyar (@dilanjaniyar_2) built his personal branding through TikTok as an entertainment content creator with his unique skills and humorous and unique behavior as his strengths. The aim of this research is to analyze Dilan Janiyar's personal branding on the content of the TikTok account @dilanjaniyar_2. This research uses a qualitative method with a qualitative descriptive approach. This research is supported by Peter Montoya's eight main concepts of personal branding, 1) specialization, 2) leadership, 3) personality, 4) distinctiveness, 5) visibility, 6) unity, 7) persistence, 8) goodwill. The data collection technique in this research uses three methods such as observation, interviews and documentation. The results of this research can be concluded that Dilan Janiyar's personal branding fulfills the eight main concepts. Having a distinctive and strong character can form a unique and positive self-image from the audience's point of view.